Fast Self‐Assembly of Photonic Crystal Hydrogel for Wearable Strain and Temperature Sensor (Small Methods 7/2022). Issue 7 (20th July 2022) - Liu, Haiyang; Wang, Yan; Shi, Zhekun; Tan, Di; Yang, Xichen; Xiong, Lingheng; Li, Gang; Lei, Yifeng; Xue, Longjian
Abstract : Photonic Crystals In article number 2200461, Lei, Xue, and co‐workers develop a fast self‐assembly method for photonic crystals. The self‐assembly can be finished within 4 hours, and the resultant photonic crystals show excellent structural colors in the visible light range. Moreover, with integration of hydrogel, the photonic crystal hydrogel functionalizes as a wearable strain sensor and temperature sensor with intuitive color outputs.